Career Development of Students Through Career Counseling Services Based on Maslow's Theory: A Systematic Literature Review (SLR) Study - Serios, Jonavie N (JURNAL KONSELING GUSJIGANG, 2023)
Career development of students in schools requires appropriate interventions to facilitate their career development process. One effective approach is through career counseling services based on Maslow's theory, which emphasizes the fulfillment of hierarchical needs to achieve individual potential to the fullest. This study uses the Systematic Literature Review (SLR) methodology to review various publications in the last five years that discuss the application of Maslow's theory in career counseling services for students. The results of the study indicate that career counseling services based on Maslow's theory are effective in helping students meet their basic needs, increasing motivation, and facilitating the achievement of more focused career goals. These findings contribute to the development of more adaptive and holistic career counseling practices in educational settings.